2020
DOI: 10.1083/jcb.201906039
|View full text |Cite
|
Sign up to set email alerts
|

Mps1-mediated release of Mad1 from nuclear pores ensures the fidelity of chromosome segregation

Abstract: The spindle assembly checkpoint (SAC) relies on the recruitment of Mad1-C-Mad2 to unattached kinetochores but also on its binding to Megator/Tpr at nuclear pore complexes (NPCs) during interphase. However, the molecular underpinnings controlling the spatiotemporal redistribution of Mad1-C-Mad2 as cells progress into mitosis remain elusive. Here, we show that activation of Mps1 during prophase triggers Mad1 release from NPCs and that this is required for kinetochore localization of Mad1-C-Mad2 and robust SAC si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…Interestingly, partial MPS1 inhibition further increases MAD1(2EK) co‐localization with TPR. This is consistent with recent work by Cunha‐Silva et al (), which shows that MPS1‐mediated phosphorylation of Drosophila melanogaster TPR disrupts its ability to bind MAD1 and is essential for kinetochore localization of MAD1 at levels required for robust SAC signaling and faithful chromosome segregation. How cyclin B1‐CDK1 cooperates with MPS1 in promoting MAD1 dissociation from TPR remains to be determined.…”
Section: The Cyclin B1‐mad1 Interaction Promotes Checkpoint Signalingsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, partial MPS1 inhibition further increases MAD1(2EK) co‐localization with TPR. This is consistent with recent work by Cunha‐Silva et al (), which shows that MPS1‐mediated phosphorylation of Drosophila melanogaster TPR disrupts its ability to bind MAD1 and is essential for kinetochore localization of MAD1 at levels required for robust SAC signaling and faithful chromosome segregation. How cyclin B1‐CDK1 cooperates with MPS1 in promoting MAD1 dissociation from TPR remains to be determined.…”
Section: The Cyclin B1‐mad1 Interaction Promotes Checkpoint Signalingsupporting
confidence: 93%
“…One plausible scenario is that cyclin B1‐CDK1 phosphorylates MPS1 to potentiate MPS1 activity at the inner nuclear pore (Morin et al , ). Overall, the findings by Jackman et al () and Cunha‐Silva et al () reveal a mechanism that coordinates cyclin B1‐CDK1‐mediated activation of APC/C at mitotic entry with its immediate inhibition by kinetochore‐based SAC signaling (Fig ).…”
Section: The Cyclin B1‐mad1 Interaction Promotes Checkpoint Signalingmentioning
confidence: 86%
“…These studies have implicated the Plk1 and Nek kinases working in coordination with Cdk1 to phosphorylate the core NPC components Nup98 and Nup53. Moreover, a recently published study revealed an important role for the MPS1 kinase in releasing MAD1 and MAD2 from the nuclear pores through phosphorylating TPR in Drosophila (Cunha-Silva et al, 2020). Our study indicates that this is likely to be conserved in evolution, and reveals that MPS1 is coordinated with Cdk1 in freeing MAD1 from TPR at the inner-NPC “basket.”…”
Section: Discussionmentioning
confidence: 99%
“…During interphase, Mad1-c-Mad2 heterotetramers localize to the NPCs and even though this association is evolutionarily conserved, [30,31,[67][68][69][70][71][72][73][74]75,76] its functional relevance remains contentious. In budding yeast, which undergoes a closed mitosis, NPC-bound Mad1 regulates nuclear import in response to kinetochore-microtubule detachment.…”
Section: A Nuclear Pore-centric View Of Mad1-c-mad2mentioning
confidence: 99%
“…This subcellular redistribution of Mad1-c-Mad2 is driven by a multi-target phosphorylation cascade orchestrated by Mps1 and Cdk1-Cyclin B1 and is required to ensure immediate inhibition of the APC/C following NE breakdown. [30,31] A detailed view of Mad1-c-Mad2 spatiotemporal regulation is explained below.…”
Section: Introductionmentioning
confidence: 99%